STUDI PERUBAHAN FONEM PADA MORFEM DENGAN TUNTUTAN LITERER DALAM LAGU “LESTARI” OLEH WAHYU F. GIRI - Mastuti, Nia; Putri, Destyani Anggia Winarno (Universitas Sebelas Maret, 2025)
Morphology, as a branch of linguistics, studies the structure of words and changes in meaning, where morphemes and allomorphs play a crucial role. Traditional Javanese songs, which have undergone transformations through reinterpretation by young artists, capture the attention of a new generation and demonstrate the cultural relevance of Javanese heritage in the digital era. This study employs a qualitative method with a discourse analysis approach to identify phonemic changes in the lyrics of the song